PENYEBAB ANAK PUTUS SEKOLAH DI JORONG TARATAK NAGARI SURANTIH KECAMATAN SUTERA KABUPATEN PESISIR SELATAN - Indra, Tomi - (Pendidikan Sosiologi, 2014)
The background of this research by the Children Out of School in Nagari Taratak Jorong Surantih Sutera Kecamatan of Selatan Pesisir Kabupaten are still many children who are not able to complete an education levels, so it can not continue their studies to the next level of education, this study aimed to describe the cause of Children Out of School in Jorong Taratak Nagari Surantih District of Sutera selatan Pesisir Kecamatan. The approach used in this study is a qualitative approach. And descriptive research informants were parents of children who drop out of school, and the community around children who have Jorong Taratak Drop out in Nagari Surantih Sutera Kecamatan of Selatan Pesisir Kabupaten, the selection of informants in this study using purposive sampling technique, the data type of the data used primary and secondary data. Data collection techniques are observation, interviews, documentation search. the unit of analysis is the family that parents of children who drop out of school. Data analysis using the principles of Miller and Huberman that includes three phases: (1) data collection data, (2) data reduction, (3), the presentation of the data. (4) drawing conclusions and verification. These results indicate that the causes of school drop out children in Jorong Taratak Nagari Surantih Sutera Kecamatan of Selatan Pesisir Kabupaten is caused by external factors (a) the geographical conditions, (b) the influence of peers, (c) Economic factors, (d) family factors, (e ) Transfortasi difficulty. The conclusion of this study that although the cause of school drop outs in Jorong Taratak Nagari Surantih Sutera Kecamatan of Selatan Pesisir Kabupaten is caused by external factors.